UPAYA MENINGKATKAN AKTIVITAS BELAJAR SISWA PADA MATA PELAJARAN AKIDAH AKHLAK DENGAN MENERAPKAN STRATEGI PEMBELAJARAN ROLE REVERSAL QUESTIONS KELAS IX MTS AL-MUTTAQIN PEKANBARU - Ali Bosar (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This research is motivated by the low level of learning activities in the akidah akhlah class IX MTs Al-MuttaqinPekanbaru. This study aims to improve the learning activities of morality through role reversal learningstrategies. The form of research is classroom action research. The subjects of this study were all students ofclass IX of MTs Al-Muttaqin Pekanbaru totaling 37 people. This research instrument consists of performanceinstruments and data collection instruments in the form of observation sheets of teacher activities and studentactivities. The results showed that the application of role revearsal questions learning strategies could increasethe activity of students in the Moral Akidah lesson as evidenced by an increase in learning activities prior to theaction to cycle I and cycle II. Before the actions are categorized as low with student learning activities a score of402 is in the very low category. And in the first cycle the first meeting got a score of 464 in the very low categoryand at the second meeting got a score of 643 in the low category. While at the first meeting the second cycle gota score of 782 in the high category and the second meeting increased with the acquisition of 928 in the very highcategory. And the success rate achieved is 89% or 928/1036 times 100 equals 89% of the total number ofstudents, meaning that almost all students have achieved predetermined success scores (minimum 75%). Basedon the results of the study, it can be concluded that the forwarding of role revearsal questions learning strategiescan improve the learning activities of the Akidah Akhlah subjects in grade IX MTs Al-Muttaqin Pekanbarustudents.